SIRT1 is regulated by a PPARγ-SIRT1 negative feedback loop associated with senescence - Han, Limin; Zhou, Rui; Niu, Jing; McNutt, Michael A; Wang, Pan; Tong, Tanjun (Nucleic acids research, 2010)
Human Silent Information Regulator Type 1 (SIRT1) is an NAD⁺-dependent deacetylase protein which is an intermediary of cellular metabolism in gene silencing and aging. SIRT1 has been extensively investigated and shown to delay senescence; however, less is known about the regulation of SIRT1 during aging. In this study, we show that the peroxisome proliferator-activated receptor-γ (PPARγ), which is a ligand-regulated modular nuclear receptor that governs adipocyte differentiation and inhibits cellular proliferation, inhibits SIRT1 expression at the transcriptional level. Moreover, both PPARγ and SIRT1 can bind the SIRT1 promoter. PPARγ directly interacts with SIRT1 and inhibits SIRT1 activity, forming a negative feedback and self-regulation loop. In addition, our data show that acetylation of PPARγ increased with increasing cell passage number. We propose that PPARγ is subject to regulation by acetylation and deacetylation via p300 and SIRT1 in cellular senescence. These results demonstrate a mutual regulation between PPARγ and SIRT1 and identify a new posttranslational modification that affects cellular senescence.